Answer :

altavistard

Answer:

1

Step-by-step explanation:

Given  f(x) = 2x^2 + x and g(x) = 3x + 2,

                                     2x^2

the quotient (f/g)(x) is -----------

                                     3x + 2

which cannot be reduced.  But we can evaluate this at x = 2:

                               

                                     2x^2         2(2)^2       2(4)             8

the quotient (f/g)(2) is ----------- = ------------- = --------- = --------- = 1

                                     3x + 2       3(2) + 2      6 + 2          8

Other Questions